IDENTIFICATION OF CONSTRUCTION TOOLS OF FISHING ACTIVITIES ACTIVE AND PASSIVE REVOLUTION KUALA KAMPAR DISTRICT PELALAWAN PROVINSI RIAU - Dessi Arisandy; Pareng Rengi; Isnaniah Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research has been conducted in February-March 2017, in Kecamatan Kuala Kampar Pelalawan District, Riau Province. This study aims to compile information and produce an efficient and efficient design of active and passive fishing equipment through an assessment of the construction of fishing gear used by fishermen in Kuala Kampar Sub-district. While the benefits of this research as an information about the identification of construction and design of fishing gear for parties that require especially for fishermen, especially in new fishing technology and business development of the way of making and produce construction and design of fishing gear. The research method used is survey method that is to conduct direct measurement of the components of active and passive fishing equipment used by fishermen and also conducted interviews directly to fishermen in Kuala Kampar waters. Based on the results of field research in Kampar kuala subdistrict, there are semi active and passive fishing tools used by fishermen. Active fishing gear such as fishing net and nets, while passive catch tools such as longlines and waves. The construction and design of active and passive fishing gear in Kecamatan kuala kampar is still simple. The absence of changes in the size of fishing gear and the design of modern fishing gear that dikecamatan kuala kampar because fishermen still follow the making of fishing gear is down.Key words : Identification of active and passive fishing gear, active and passive capture design.